Additional electron pairing in a d-wave superconductor driven by nematic order - Jing-Rong Wang; Guo-Zhu Liu (New Journal of Physics, 2013)
We perform a non-perturbative analysis of the strong interaction between gapless nodal fermions and the nematic order parameter in two-dimensional d _x ^2_2 _− _y ^2_2 superconductors. We predict that the critical nematic fluctuation can generate a dynamical nodal gap if the fermion flavor N is smaller than a threshold N _c . Such gap generation leads to an additional is-wave Cooper pairing instability, which induces a fully gapped d _x ^2_2 _− _y ^2_2  +  is superconducting dome in the vicinity of the nematic quantum critical point. The opening of a dynamical gap has important consequences, including the saturation of fermion velocity renormalization, a weak confinement of fermions and the suppression of observable quantities.